Does exercise have healing and preventive roles in COVID-19 pandemic? - Patlar, Süleyman; Unal, Bahar; Bakum, Abdullah; Böge, Veysel (Journal of Surgery and Medicine, 2021)
The COVID-19 pandemic caused by the SARS-CoV-2 virus, which occurred in Wuhan in China on December 31, 2019, spread rapidly to 6 continents and hundreds of countries. Scientists continue to work on effective treatment protocols and vaccine development to stop the spread of this pandemic. Currently, anti-virus strategies are as important as treatment methods. It is known that physical exercise is one of the pillars of a healthy life and reduces the risk of developing non-infectious diseases which endanger the immune system significantly. Besides, regular moderate intensity exercise has preventive effects against cardiovascular diseases, respiratory tract infections, obesity, and diabetes. In this review, we aimed to discuss whether physical activity has a protective effect and present new information to ameliorate the wellbeing of individuals during the pandemic, so they are less affected by COVID-19. From this point of view, experimental and clinical studies on this subject were analyzed. Literature reviews showed that maintaining physical exercise during the COVID-19 outbreak is crucial for the recovery of patients with obesity, lung, and heart diseases. However, it can be said that asymptomatic young and middle-aged individuals with positive COVID-19 tests can overcome the disease more easily and in a shorter time.